Airpower and technology : smart and unmanned weapons - Mets, David R. (Praeger Security International, 2009)
Since its earliest days, airpower has been one of the dominant forces used by the American military. This work covers the whole history of American aviation with special attention to the development of smart weapons and unmanned aerial vehicles and the influence they have had on the effectiveness of airpower. In a chronological treatment, emphasizing theory and doctrine, technology, tactics, and strategy. Mets details both combat experience and intellectual processes, lethal and non-lethal, involved in the preparation of airpower. In addition to the narrative discussion, the work offers sideba.